Konsep pendidikan Ki Hadjar Dewantara dan implementasinya di Sekolah Dasar di Indonesia - Harini, Rochmimah; Istiq’faroh, Nurul; Hendratno (CV. Kurnia Grup, 2023)
This research aims to explore the essence of Ki Hajar Dewantara's educational thinking and its relevance to the world of modern education as an educational pioneer. Ki Hajar Dewantara, or his full name Raden Mas Soewardi Soerjaningrat, is an Indonesian educational figure who has made a major contribution to the development of education in Indonesia. One of the theories he developed was